Pollinator habitat enhancement through ornamental plants, floral traits and urban green area features for planning biodiversity-friendly cities - Paolo Biella; Giulia Brambilla; Valentina Verduci; Matteo Annessi; Andrea Beltramini; Lorenzo Bianco; Daniele Calabrese; Francesca Romana Dani; Marta Depetris; Andrea Di Giulio; Andrea Ferrari; Jessica Frigerio; et al. (Landscape and Urban Planning, 2026)

Perceived Impact of Site Personnel and Infrastructure on Monitoring Quality in Clinical Trials: a Survey of Italian CRA/CTM Professionals - Stefano Stabile; Sara Testoni; Emanuela Scarpi; Veronica Franchina; Francesca Mannozzi; Marta Betti; Alessandra Ferrari; Celeste Cagnazzo (Journal of Pharmaceutical Innovation, 2026)

Correction to: Impact of Regulation (EU) No. 536/2014 on clinical trial approval processes in two Italian oncology centers - Daniela Bencardino; Fabiana Marchetti; Cristina Mazzi; Marianna Ferrari; Francesca Garibaldi; Giulia Ferrera; Giulia Ponti; Chiara Altavilla; Laura Rossi; Matteo Verzè; Vanda Salutari; Vincenzina Mora; et al. (Journal of Pharmaceutical Innovation, 2026)

Circulating metabolites and fatty acids associated with ultra-processed food consumption: results from the EPIC study - Jessica Blanco-Lopez; Sahar Yammine; Joseph A. Rothwell; Mathilde His; Carine Biessy; Pekka Keski-Rahkonen; Bernadette Chimera; Inarie Jacobs; Aline Al Nahas; Emine Koc Cakmak; Oliver Robinson; Fernanda Morales Berstein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Impact of Regulation (EU) No. 536/2014 on clinical trial approval processes in two Italian oncology centers - Daniela Bencardino; Fabiana Marchetti; Cristina Mazzi; Marianna Ferrari; Francesca Garibaldi; Giulia Ferrera; Giulia Ponti; Chiara Altavilla; Laura Rossi; Matteo Verzè; Vanda Salutari; Vincenzina Mora; et al. (Journal of Pharmaceutical Innovation, 2026)

Oral exposure to micro- and nanoplastics: Developing a modular and flexible risk assessment framework for human health - Amelie Vogel; Holger Sieg; Linda Böhmert; Annemijne van den Berg; Valerie Fessard; Francesca Ferraris; Raymond Pieters; Francesco Cubadda; Andrea Haase (Food and Chemical Toxicology, 2026)

Perceived greenwashing: where does scepticism come from? - Francesca Romana Rinaldi; Fahimeh Khatami; Enrico Cagno; Alberto Ferraris (Journal of Cleaner Production, 2026)

Generative artificial intelligence and marine ecological monitoring - Luciano Ortenzi; Jacopo Aguzzi; Damianos Chatzievangelou; Eugenio Nerio Nemmi; Michele Ferrari; Ivan Masmitja; Morane Clavel-Henry; Nixon Bahamon; Nathan J. Robinson; Giacomo Picardi; Paula Espina; Simona Violino; et al. (Environmental Modelling & Software, 2026)

Development and validation of an LC-HRMS method for the determination of monomers of wine fining PVPP and PVI-PVP polymers - Francesca Borghini; Stefano Ferrari; Alessandro Cavaglioni; Marco Consumi; Gabriella Tamasi; Federico Guidugli (Food Chemistry, 2025)

A journey of discovery: a multi-stage diagnostic procedure identifies Curtobacterium flaccumfaciens pv. allii as a new potential threat to maize - Francesca Gaffuri; Irene Ferraris; Alessia Follador; Alessia Travaglino; Luca Angheben; Antonina Rita Limongi; Alessandro Passera; Beniamino Cavagna; Piero Attilio Bianco; Massimo Delledonne; Paola Casati (Crop Protection, 2025)

A genetic algorithm-based approach for quantitative prediction of drug-drug interactions caused by cytochrome P450 3A inhibitors and inducers in dogs and cats - Veronica Di Paolo; Francesco Maria Ferrari; Italo Poggesi; Mauro Dacasto; Francesca Capolongo; Luigi Quintieri (Chemico-Biological Interactions, 2025)

Contaminant-driven midgut histological damage in bees and other aculeate Hymenoptera: A quantitative review - Carlo Polidori; Chiara Francesca Trisoglio; Andrea Ferrari; Andrea Romano; Francesco Bonasoro (Environmental Toxicology and Pharmacology, 2025)

Unlocking the Potential of Marine Sidestreams in the Blue Economy: Lessons Learned from the EcoeFISHent Project on Fish Collagen - Lorenzo Dondero; Giulia De Negri Atanasio; Francesca Tardanico; Erica Lertora; Raffaella Boggia; Vittorio Capra; Agnese Cometto; Mattia Costamagna; Fi.L.S.E; Mirvana Feletti; Fulvio Garibaldi; Federica Grasso; et al. (Marine Biotechnology, 2025)
This review provides a general overview of collagen structure, biosynthesis, and biological properties, with a particular focus on marine collagen sources, especially fisheries discards and by-catches. Additionally, well-documented applications of collagen are presented, with special emphasis not only on its final use but also on the processes enabling sustainable and safe recovery from materials that would otherwise go to waste. Particular attention is given to the extraction process, highlighting key aspects essential for the industrialization of fish sidestreams, such as hygiene standards, adherence to good manufacturing practices, and ensuring minimal environmental impact. In this context, the EcoeFISHent projects have provided valuable insights, aiming to create replicable, systemic, and sustainable territorial clusters based on a multi-circular economy and industrial symbiosis. The main goal of this project is to increase the monetary income of certain categories, such as fishery and aquaculture activities, through the valorization of underutilized biomass.

A screening method for detection of TiO2 in food based on Raman spectroscopy and its applicability in a regulatory context - Ivana Bianchi; Hind El Hadri; Otmar Geiss; Karlien Cheyns; Jan Mast; Francesca Ferraris; Francesco Cubadda; Khouloud El Hanafi; Jean-Philippe Rosec; Francois Auger; Josefa Barrero-Moreno (Food Control, 2025)

From molecules to organisms: A multi-level approach shows negative effects of trace elements from sewage sludge used as soil improver on honeybees - Andrea Ferrari; Michela Sturini; Beatrice De Felice; Francesco Bonasoro; Chiara Francesca Trisoglio; Marco Parolini; Roberto Ambrosini; Luca Canova; Antonella Profumo; Federica Maraschi; Carlo Polidori; Alessandra Costanzo (Journal of Hazardous Materials, 2024)

Multichannel GPR and multi-depth electromagnetic surveys for the study of Villa Eucheria and Aquinum at Castrocielo (Frosinone, Central Italy) - Dora Francesca Barbolla; Ivan Ferrari; Francesco Giuri; Ilaria Miccoli; Giuseppe Scardozzi; Veronica Ferrari; Giovanni Leucci (Journal of Applied Geophysics, 2024)

Clay mineralogy in west Chryse Planitia, Mars: Comparison with present and future landing sites - Jeremy Brossier; Francesca Altieri; Maria Cristina De Sanctis; Alessandro Frigeri; Marco Ferrari; Simone De Angelis; Enrico Bruschini (Planetary and Space Science, 2024)

Using stable isotopes to inform water resource management in forested and agricultural ecosystems - Francesca Scandellari; Taha Attou; Adrià Barbeta; Fabian Bernhard; Concetta D’Amato; Katya Dimitrova-Petrova; Amanda Donaldson; Oludare Durodola; Stefano Ferraris; Marius G. Floriancic; Gabriela Fontenla-Razzetto; Malkin Gerchow; et al. (Journal of Environmental Management, 2024)

Villa del Casale Piazza Armerina (EN): New data related to geophysical investigations - Isabella Baldini; Carla Sfameni; Lara De Giorgi; Dora Francesca Barbolla; Ivan Ferrari; Francesco Giuri; Chiara Torre; Giovanni Leucci (Journal of Applied Geophysics, 2024)

Preliminary spectroscopic investigation of a potential Mars analog site: Lake Bagno dell’Acqua, Pantelleria, Italy - Enrico Bruschini; Marco Ferrari; Cristina Mazzoni; Stefano Fazi; Francesco Latino Chiocci; Ilaria Mazzini; Giovanna Costanzo; Simone De Angelis; Maria Cristina De Sanctis; Francesca Altieri; Jeremy Brossier; Eleonora Ammannito (Planetary and Space Science, 2024)

Short-chain fatty acids modulate the IPEC-J2 cell response to pathogenic E. coli LPS-activated PBMC - Melania Andrani; Luca Ferrari; Paolo Borghetti; Valeria Cavalli; Elena De Angelis; Francesca Ravanetti; Eleonora Dall'Olio; Paolo Martelli; Roberta Saleri (Research in Veterinary Science, 2024)

Serum from COVID-19 patients promotes endothelial cell dysfunction through protease-activated receptor 2 - Francesco Vieceli Dalla Sega; Francesca Fortini; Danilo Licastro; Simeone Dal Monego; Margherita Degasperi; Alessia Ascierto; Luisa Marracino; Paolo Severi; Maria D’Accolti; Irene Soffritti; Marta Brambilla; Marina Camera; et al. (Inflammation Research, 2024)

Efficient utilization of monosaccharides from agri-food byproducts supports Chlorella vulgaris biomass production under mixotrophic conditions - Francesca Angelini; Erika Bellini; Angela Marchetti; Gaia Salvatori; Marianna Villano; Daniela Pontiggia; Simone Ferrari (Algal Research, 2024)

Osmolarity modulates the de-differentiation of horse articular chondrocytes during cell expansion in vitro: implications for tissue engineering in cartilage repair - Elena De Angelis; Amelia Barilli; Roberta Saleri; Bianca Maria Rotoli; Francesca Ravanetti; Francesca Ferrari; Luca Ferrari; Paolo Martelli; Valeria Dall’Asta; Paolo Borghetti (Veterinary Research Communications, 2023)

A multidisciplinary approach to estimating wolf population size for long‐term conservation - Francesca Marucco; Maria V. Boiani; Pierre Dupont; Cyril Milleret; Elisa Avanzinelli; Kristine Pilgrim; Michael K. Schwartz; Achaz von Hardenberg; Domenica Serena Perrone; Olivier P. Friard; Arianna Menzano; Francesco Bisi; et al. (Conservation Biology, 2023)
The wolf ( Canis lupus ) is among the most controversial of wildlife species. Abundance estimates are required to inform public debate and policy decisions, but obtaining them at biologically relevant scales is challenging. We developed a system for comprehensive population estimation across the Italian alpine region (100,000 km 2 ), involving 1513 trained operators representing 160 institutions. This extensive network allowed for coordinated genetic sample collection and landscape‐level spatial capture–recapture analyses that transcended administrative boundaries to produce the first estimates of key parameters for wolf population status assessment. Wolf abundance was estimated at 952 individuals (95% credible interval 816–1120) and 135 reproductive units (i.e., packs) (95% credible interval 112–165). We also estimated that mature individuals accounted for 33–45% of the entire population. The monitoring effort was spatially estimated thereby overcoming an important limitation of citizen science data. This is an important approach for promoting wolf–human coexistence based on wolf abundance monitoring and an endorsement of large‐scale harmonized conservation practices.

Mechanical power normalized to aerated lung predicts noninvasive ventilation failure and death and contributes to the benefits of proning in COVID-19 hypoxemic respiratory failure - Giovanni Musso; Claudio Taliano; Marco De Iuliis; Elena Paschetta; Caterina Fonti; Andrea Ferraris; Marta Druetta; Ines Sarah Vianou; Francesca Ranghino; Federica Riedo; Davide Deangelis; Gloria Tirabassi (EPMA Journal, 2023)

Life cycle assessment for the production of MSWI fly-ash based porous glass-ceramics: Scenarios based on the contribution of silica sources, methane aided, and energy recoveries - Francesco Barracco; Francesca Demichelis; Elham Sharifikolouei; Monica Ferraris; Debora Fino; Tonia Tommasi (Waste Management, 2023)

Simultaneous extraction of calcium phosphates and proteins from fish bones. Innovative valorisation of food by-products - Alessio Adamiano; Stefania Scialla; Francesca Carella; Marialuisa Casella; Serena Camerini; Alessandra Quarta; Alexandra Muntiu; Francesca Ferrari; Alberto Vitali; Michele Iafisco; Clara Piccirillo (Journal of Cleaner Production, 2023)

Peripheral neuropathies during the COVID-19 pandemic: is there a relation? - Milena Trentinaglia; Giuseppe Lippi; Gian Luca Salvagno; Marianna G. Rispoli; Maria Vittoria De Angelis; Francesca Castellani; Daniela Alberti; Giorgia T. Maniscalco; Francesca Rossi; Mara Turri; Patrizia Rossi; Elisabetta Del Zotto; et al. (Immunologic Research, 2022)

Invading parasites: spillover of an alien nematode reduces survival in a native species - Claudia Romeo; Anna Pia Piscitelli; Francesca Santicchia; Adriano Martinoli; Nicola Ferrari; Lucas A. Wauters (Biological Invasions, 2021)
It is widely assumed that spillover of alien parasites to native host species severely impacts naïve populations, ultimately conferring a competitive advantage to invading hosts that introduced them. Despite such host-switching events occurring in biological invasions, studies demonstrating the impact of alien macroparasites on native animal hosts are surprisingly few. In Europe, native red squirrels ( Sciurus vulgaris) are replaced by introduced North American grey squirrels ( S. carolinensis ) mainly through resource competition, and, only in the United Kingdom and Ireland, by competition mediated by a viral disease. In Italy such disease is absent, but spillover of an introduced North American nematode ( Strongyloides robustus ) from grey to red squirrels is known to occur. Here, we used long-term (9 years) capture-mark-recapture and parasitological data of red squirrels in areas co-inhabited by grey squirrels in Northern Italy to investigate the impact of this alien helminth on naïve native squirrels’ body mass, local survival, and reproduction of females. We found no negative effect of the alien parasite on body mass or reproductive success, but intensity of infection by S. robustus reduced survival of both male and female squirrels. Significantly, survival of squirrels co-infected by their native nematode, Trypanoxyuris sciuri , was less affected by S. robustus , suggesting a protective effect of the native helminth against the new infection. Hence, we demonstrate that alien S. robustus spillover adds to the detrimental effects of resource competition and stress induced by grey squirrels, further reducing the fitness of the native species in the presence of the invasive competitor.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

“My Husband Affects Me More Than My Cancer”: Reflections on Simultaneous Intimate Partner Violence and Breast Cancer Experience in a 48-Year-Old Woman - Francesca Dionigi; Valentina Martinelli; Eugenia Trotti; Alberta Ferrari; Carlos Alberto Garcia-Etienne; Angelica Della Valle; Donatella Grasso; Elisa Ferraris; Gianpiero Rizzo; Vincenza Praticò; Adele Sgarella (Journal of Cancer Education, 2020)

New Platinum-Based Prodrug Pt(IV)Ac-POA: Antitumour Effects in Rat C6 Glioblastoma Cells - Beatrice Ferrari; Francesca Urselli; Martina Gilodi; Serena Camuso; Erica Cecilia Priori; Beatrice Rangone; Mauro Ravera; Paola Veneroni; Ilaria Zanellato; Elisa Roda; Domenico Osella; Maria Grazia Bottone (Neurotoxicity Research, 2020)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

The preload force affects the perception threshold of muscle vibration-induced movement illusions - Francesca Ferrari; Francesco Clemente; Christian Cipriani (Experimental Brain Research, 2019)

Trans-splicing of plastid rps12 transcripts, mediated by AtPPR4, is essential for embryo patterning in Arabidopsis thaliana - Luca Tadini; Roberto Ferrari; Marie-Kristin Lehniger; Chiara Mizzotti; Fabio Moratti; Francesca Resentini; Monica Colombo; Alex Costa; Simona Masiero; Paolo Pesaresi (Planta, 2018)

Cortical and subcortical connections of parietal and premotor nodes of the monkey hand mirror neuron network - Stefania Bruni; Marzio Gerbella; Luca Bonini; Elena Borra; Gino Coudé; Pier Francesco Ferrari; Leonardo Fogassi; Monica Maranesi; Francesca Rodà; Luciano Simone; Francesca Ugolotti Serventi; Stefano Rozzi (Brain Structure and Function, 2017)

Identification of an atypical microdeletion generating the RNF135-SUZ12 chimeric gene and causing a position effect in an NF1 patient with overgrowth - Luca Ferrari; Giulietta Scuvera; Arianna Tucci; Donatella Bianchessi; Francesco Rusconi; Francesca Menni; Elena Battaglioli; Donatella Milani; Paola Riva (Human Genetics, 2017)

Membrane proteome functional characterization of breast cancer-initiating cells subjected to bone morphogenetic protein signaling inhibition by dorsomorphin - Susy Piovesana; Anna Laura Capriotti; Valentina Colapicchioni; Francesca Ferraris; Giorgia La Barbera; Salvatore Ventura (Medicinal Chemistry Research, 2016)

IL-4 Release from a Biomimetic Scaffold for the Temporally Controlled Modulation of Macrophage Response - Silvia Minardi; Bruna Corradetti; Francesca Taraballi; Jae Hyuk Byun; Fernando Cabrera; Xeuwu Liu; Mauro Ferrari; Bradley K. Weiner; Ennio Tasciotti (Annals of Biomedical Engineering, 2016)

Detectability of Fast Ripples (>250 Hz) on the Scalp EEG: A Proof-of-Principle Study with Subdermal Electrodes - Francesca Pizzo; Birgit Frauscher; Taissa Ferrari-Marinho; Mina Amiri; Francois Dubeau; Jean Gotman (Brain Topography, 2016)

Simulation of the January 2014 flood on the Secchia River using a fast and high-resolution 2D parallel shallow-water numerical scheme - Renato Vacondio; Francesca Aureli; Alessia Ferrari; Paolo Mignosa; Alessandro Dal Palù (Natural Hazards, 2016)

Neuromelanin of the Human Substantia Nigra: An Update - Fabio A. Zucca; Emy Basso; Francesca A. Cupaioli; Emanuele Ferrari; David Sulzer; Luigi Casella; Luigi Zecca (Neurotoxicity Research, 2014)

Holoprosencephaly: report of four cases and genotype–phenotype correlations - FRANCESCA LAMI; DIANA CARLI; PAOLA FERRARI; MONICA MARINI; VIOLA ALESI; LORENZO IUGHETTI; ANTONIO PERCESEPE (Journal of Genetics, 2013)

Synthesis and characterization of glucosyl-curcuminoids as Fe3+ suppliers in the treatment of iron deficiency - Erika Ferrari; Beatrice Arezzini; Marco Ferrali; Sandra Lazzari; Francesca Pignedoli; Ferdinando Spagnolo; Monica Saladini (BioMetals, 2009)

Intestinal helminth communities of the red fox (Vulpes vulpes L.) in the Italian Alps - Anna Cerbo; Maria Manfredi; Karin Trevisiol; Marco Bregoli; Nicola Ferrari; Francesca Pirinesi; Selvaggia Bazzoli (Acta Parasitologica, 2008)
The study analyses the intestinal helminth communities found in 645 red foxes of alpine populations from five areas of Northern Italy. In particular, the aim was to evaluate the contribution of both environmental variability and the structure of fox population (extrinsic and intrinsic factors, respectively) in shaping the structure and composition of the intestinal helminth communities. To identify the influence of the characteristics of the host (i.e. age and sex) together with extrinsic factors (year, site, season, and altitude of collection) on number of species, total load per fox, prevalence and abundance of each parasite species, general linear models were performed. Fifteen helminth species have been detected in the intestine of 545 infected animals (84.5%) with a total of 17,144 parasites collected. The analysis of factors influencing both prevalence and abundance of infection of the parasite species revealed the preponderance of extrinsic factors on intrinsic ones. In particular, geographical areas influenced prevalence and abundance of every parasite species, showing high spatial variability. The lower influence of host factors may suggest that, in this case, host dynamics play a trivial role with respect to spatial variability in determining parasite abundance. These results pointed out high prevalence of intestinal helminth infections in the Italian Alpine fox, confirmed the typical composition of parasite fauna within fox populations, underlined local differences in the structure and composition of the helminth communities. Moreover, this study highlights the major role of extrinsic factors vs intrinsic ones.